Towards the Origins of the Concentration of the Media in Argentina - Bernadette Califano (Íconos)
This article sets out to critically examine the origins of the process of the concentration of media in Argentina through a study of the communication policies implemented in the framework of the adoption of the neoliberal economic model. For this, an analysis is carried out of the investment conformation and of the evolution in terms of invoicing and business ranking of the media groups that obtained the licenses for the open television canals in the city of Buenos Aires after their transfer into private hands. An evaluation is made of the extent to which the particular characteristics of this privatization resulted in economic benefits for the awarded businesses and influenced the configuration of the map of Argentinian media.